The role of credit in the housing market - Petra Gerlach-Kristen; Niall McInerney (The Economic and Social Research Institute (ESRI), 2014)
We estimate a structural model of the Irish housing and mortgage markets and isolate the role of demand and supply factors in each market. We focus on the pre-2004 period during which house prices and mortgage credit exhibited a stable relationship. We find that mortgage demand is determined by interest rates, income and house price growth while mortgage supply is mainly a function of deposits. We show that the demand for housing is predominantly driven by house prices, mortgage credit and demographics and that supply depends on the profitability of housing construction. We then use the model to forecast how these markets will develop based on different scenarios about the model's exogenous variables. The high-growth scenario sees house prices rising by 50 percent over the next decade with an annual increase in the housing stock of 18,500 units.
Keywords: 330; house prices; mortgage credit; simultaneous equations; simulation